The Effect of Interactive Board Games (IBG) on Vocabulary Achievement - Endang Sulistianingsih; Rizka Febriani; Jcs Pradjarto (Langkawi: Journal of The Association for Arabic and English, 2019)
Vocabulary Achievement is an element of learning the language which may assist students in understanding the language through basic English skills. Interactive Board Games are board games that use multimedia system (PowerPoint) teaching technique. This is often one of the traditional games that may be played by group activity and paired with a blackboard to focus on visual media activity. To find out the effect of using Interactive Board Games on students’ vocabulary achievement, we used the quantitative approach by assigning experimental research. There were two groups that we used in this research. Group one as experimental group and other as a control group. We used Total Pscycal Response (TPR) method for both groups, but we often gave Interactive Board Games to the experimental group in the learning process. There were eight meetings that we conducted into the experimental group with treatment using Interactive Board Games. We calculated the data from the test given when students learning English used Interactive Board Games. Before the test gave to the sample, the writer gave the test to students who have the same ability but not sample to know regarding validity and reliable of the test. Based on the t-test, we found that the t-ratio was higher than the t-table. The result indicated that there was a significant difference between the students who were taught using Interactive Board Games and the students who were not taught using Interactive Board Games.